Long-term effects of vaginal erbium laser in the treatment of genitourinary syndrome of menopause. (4th March 2018) - Gambacciani, M.; Levancini, M.; Russo, E.; Vacca, L.; Simoncini, T.; Cervigni, M.
Abstract: Objectives: To evaluate the long-term efficacy of a second generation of vaginal laser treatment, the vaginal erbium laser, as a non-ablative photothermal therapy for the management of genitourinary syndrome of menopause. Methods: The study was performed using an erbium laser crystal yttrium-aluminum-garnet (XS Fotona Smooth™, Fotona, Ljubljana, Slovenia) with a wavelength of 2940 nm. Postmenopausal women ( n  = 205) were treated with three laser applications at 30-day intervals. Symptoms were assessed before and after treatment throughout 24 months, using the subjective visual analog scale (VAS) and the objective vaginal health index score (VHIS). In addition, postmenopausal women suffering from stress urinary incontinence were evaluated with the International Consultation on Incontinence Questionnaire-Urinary Incontinence Short Form (ICIQ-UI SF). Results: Vaginal erbium laser treatment induced a significant ( p  < 0.01) decrease in VAS for both vaginal dryness and dyspareunia, as well an increase in VHIS ( p  < 0.01) up to the 12th month after the last laser treatment. The values returned to levels similar to the baseline after 18 and 24 months. In addition, vaginal erbium laser treatment improved mild-moderate stress urinary incontinence in 114 postmenopausal women. Less than 3% of patients discontinued treatment due to adverse events. Conclusions: These results suggest that vaginal erbium laser may be effective and safe for the treatment of genitourinary syndrome of menopause.